Assessing possibilities of conducting Community Conversations (CCs) and establishing Communities of Practices (CoP) in Biden Community, Konso, Ethiopia - Dessalegn, Bezaiet; Woldegiorgis, Mamusha; Dea, Dereje (International Center for Agricultural Research in the Dry Areas, 2023)
Participatory engagement of communities is key to establish a good understanding of conditions on the ground including prevalent challenges, to collectively identify plausible solutions, and to ensure sustainable adoption of innovative technologies and practices. Community Conversations (CCs) offer unique opportunities to facilitate dialogue among groups of a community and key local government and research institutions on selected topics of interest. Initiated through a joint ICARDA-ILRI effort and building on the Community Based breeding program (CBBP), CCs were conducted in several districts in northern and southern Ethiopia to, inclusively and collectively, identify key challenges in the management and marketing of sheep; facilitate group learning and joint analysis; and seek context-specific solutions to address them. Common topics of the CCs included community breeding, feed production and management, animal upkeep and health, antimicrobial use and resistance, marketing, and gender roles. The inclusive dialogues facilitated through CCs and the ensuing group learning and action thus present opportunities for change (Mulema et al. 2020). The CCs were subsequently complimented with the organization of Communities of Practice (CoP) that comprised of representatives of woreda-level experts in selected fields of practice including – agriculture, livestock, gender, natural resource management, animal health, socioeconomics, extension, communication, and others as needed. The CoPs created space for woreda-level inter-disciplinary dialogue, peer-learning, project and resource coordination, and promotion of integrated context-specific solutions that are in line with woreda and regional strategic plans. Multiple topic-specific modules have been developed over the years to support facilitators of CCs, as well as reports on the outcomes of the conversations held. In June of 2022, a joint ICARDA-ILRI field trip was organized to meet with members of CC groups in selected Kebeles located in Doyogena and Menz to: • assess the effectiveness of the CCs and CoPs in facilitating sustained community engagement and bringing about changes at the household and community level, • learn about prevailing technical and organizational challenges, and • explore opportunities to address selected challenges through the SAPLING Initiative Another, joint ICARDA-ILRI exploratory visit was made to Konso in November of 2022, to assess the potential to conduct action research focusing on CC induced gender transformative changes that could be reflected at the household, community, and institutional levels.